Promosi Dan Cita Rasa terhadap Kepuasan Pelanggan C’Bezt Friedchicken Jalan Kalimantan Jember - Lina Kumala Sari; Seno Sumowo; Jekti Rahayu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Understanding the influence of promotion, price and brand image on customer satisfaction C'bezt Friedchicken Kalimantan street Jember is the purpose of this study, where many customers complain about expensive prices and are not comparable to the satisfaction received, the types used are primary data and secondary data, then analytical tools using data instrument tests, multiple linear regression and classical assumption tests, The results of this study state that promotion, price and taste have a positive and significant impact on customer satisfaction at C'best friedchicken Kalimantan street Jember.